Protection of Children’s Rights in International Humanitarian Law - Dubovyk, Kateryna (Theory and Practice of Public Administration, 2022)
The article focuses on the protection of children’s rights in international humanitarian law. All over the world, thousands of children are exposed to the dangers of armed conflict. Children are recruited into the civil militia, ranks of the state army, and other military formations. Many children are abducted from schools, streets, and their homes. Some «voluntarily» join the ranks of military formations because they have no alternative: the reason for this is discrimination, numerous restrictions, poverty and other factors. Specialists in legal issues emphasize the need to prohibit the involvement and use of children, that is, persons who have not reached the age of 18, in armed conflicts. Thus, International Humanitarian Law prohibits the involvement and participation of children under the age of 15 in military operations, whether internal or international conflict. Despite this, about 200,000 child soldiers are involved in more than 20 military conflicts around the world. Hundreds of thousands of children became witnesses and participants of hostilities in Ukraine. This vulnerable group is easy to manipulate due to age-related psychological characteristics.